PENGARUH REWARD DAN MOTIVASI TERHADAP KINERJA KARYAWAN J&T EXSPRESS - Fani, Nauli; Wahyu Pril Ranto, Dwi (Universitas Boyolali, 2023)
The aim of this research is to determine the influence of reward and work motivation variables on employee performance. The research approach uses quantitative methods. The research was conducted at the J&T Express Yogyakarta branch office. The data source used is primary data. The sample used in this research consisted of 105 J&T Exspres employees. The sampling technique uses random sampling. The data collection technique uses a questionnaire. Based on the results of the instrument quality test, the results showed that all instruments used to measure research variables were declared valid and reliable. Meanwhile, based on the results of data analysis that was carried out using multiple linear regression, the results showed that reward and motivation had a positive and significant effect on employee performance. It can be concluded that the better the rewards and motivation provided, the more good employee performance will be created. Keywords: motivation; rewards; employee performance